The role of budget transparency, tax knowledge and tax education in tax compliance: Evidence from salaried and self-employed taxpayers in Malaysia - Al-Maghrebi, Mohammed Saleh; Palil, Mohd Rizal (Universitas Muhammadiyah Yogyakarta, Indonesia, 2026)
Research aims: The objective of this study is to investigate the impact of budget transparency, tax knowledge, and tax education on Tax Compliance (TC) among individual taxpayers in Malaysia. This study used a questionnaire instrument and a quantitative approach to collect data from salaried individuals and the self-employed. The relationships between independent variables and the dependent variable were examined using correlation and regression analyses to determine the extent of their impact. Design/Methodology/Approach: The study population comprised salaried and self-employed taxpayers in Malaysia. A purposive sampling technique was employed to target respondents with actual tax filing experience, including academic staff, medical practitioners, and legal professionals. These groups were selected due to their direct exposure to Malaysia’s self-assessment tax system. The questionnaire items were adapted from established studies to ensure content validity. Research findings: To fulfill the objectives, this study attempts to provide some information and results by presenting empirical evidence for Malaysian authorities, practitioners and interested parties. This will lead to improve TC amongst individual Malaysian taxpayers in the future. The findings of this research demonstrate that budget transparency has a positive and significant impact on TC. In addition, tax knowledge and tax education have influenced individual taxpayer compliance positively and significantly. Theoretical contribution/Originality: This study contributes to the tax compliance literature by integrating budget transparency, tax knowledge, and tax education within a Theory of Planned Behavior framework. The findings offer practical insights for policymakers by emphasizing the importance of transparency and taxpayer education as tools for enhancing voluntary compliance in self-assessment tax systems, particularly in developing economies such as Malaysia.Practitioner/Policy implication: The primary concern for tax authorities in both developed and developing countries is TC. As a result, professionals in academic and non-academic organizations are attempting to enhance the level of TC among taxpayers. This will lead to an increase in tax revenue figures in the national budget. To achieve this, various strategies are being implemented, such as improving taxpayers' tax knowledge and education and providing them with all possible information on the contents of the public budget, specifically concerning tax revenue and its allocation.